Pandeglang Community Mantras as Performative Knowledge: A Critical Discourse Analysis of Fairclough's Oral Tradition Model - Trisnawati, Trisnawati; Permadi, Tedi; Mulyati, Yeti; Yulianeta, Yulianeta; Anshori, Dadang S.; Sumiyadi, Sumiyadi; Nugroho, Rudi Adi (Universitas Muhammadiyah Malang, 2025)
This research is motivated by the fading of oral traditions amid modernization, particularly the mantras of the Pandeglang community, which have been viewed solely as ritual texts without literary value. The main problem this research addresses is how the representation of cultural values, power relations, and ideology is manifested in mantras, and how these texts can serve as a medium for critical literacy in secondary education. The purpose of this research is to uncover the linguistic structures, discursive practices, and social contexts that shape the discourse of mantras, while also proposing their use in strengthening cultural literacy in schools. The research uses a critical constructivist paradigm with an interpretive, qualitative approach, drawing on Norman Fairclough's Critical Discourse Analysis model and discourse ethnography. Data in the form of 11 Sundanese-Banten mantra texts were collected through participant observation, in-depth interviews, and field documentation. The analysis shows that mantras function not only as spiritual means but also as ideological discourses that reproduce the moral, spiritual, and social values of the Pandeglang community. Socially, mantras become a cultural literacy practice that strengthens local identity and power relations. At the same time, pedagogically, they have the potential to become a source of critical literacy learning in high schools. The research conclusion confirms that mantras are performative texts that contain educational, spiritual, and ideological power—a form of local literacy that remains relevant for fostering reflective awareness and cultural identity among the younger generation.